Impact of Different Sectioning of Excision Biopsies of the Cervical Transformation Zone for Detection of Invasive Cervical Cancer in 2 European Centers Related to National Cervical Screening Programs. Issue 4 (1st May 2010) - Gutnik, Helena; Fležar, Margareta Strojan; Pižem, Jože; Ellis, Kay; Don, Olivia; Perunović, Branko
Abstract : Background: The impact of the number of sections used in cervical excision biopsies of transformation zone on sensitivity of histological detection of cervical cancer is poorly documented. Aim: To assess whether different techniques of sectioning cervical excision biopsies in 2 European laboratories influence the finding of cervical cancer by histopathological examination. Materials and Methods: The routine assessment at the Department of Histopathology and Cytology, Sheffield Teaching Hospitals NHS Foundation Trust, Sheffield, UK (Sheffield), encompassed sectioning a cone in 3-mm tissue blocks and cutting 3 levels per block. At the Institute of Pathology, Faculty of Medicine, University of Ljubljana, Slovenia (Ljubljana), cones were cut in a 3- to 4-mm-thick tissue block, and 10 levels were cut per block, spaced every 100 μm. The number of blocks and levels per block were assessed for each cone. Histopathological detection of cervical carcinoma between the laboratories was compared. Results: Among 820 cones in the Sheffield laboratory, we detected 35 invasive carcinomas, whereas 6 invasive carcinomas were detected among 94 cones in the Ljubljana laboratory. Although the Slovenian laboratory examined a significantly larger number of levels per cone biopsy (64 vs 24 in Sheffield), this was not associated with a larger proportion of invasive cervical carcinoma, especially foci of stage IA1 or high-grade cervical intraepithelial neoplasia diagnosed on excision biopsies: 6.4% of invasive cervical carcinomas (5 [83.3%] of stage IA1) in Ljubljana and 4.3% (30 [85.7%] of stage IA1) in Sheffield laboratory ( P > 0.05); 71.2% of high-grade cervical intraepithelial neoplasia in Ljubljana and 75.5% in Sheffield ( P > 0.05). Conclusions: Our assessment showed that a method with a large number of levels per cervical cone or large loop excision of the transformation zone biopsy did not increase sensitivity for the detection of cervical cancer. However, extensive sectioning substantially affects the pathologist's workload, and this may need to be reconsidered.